Save Spanish working class revolutionaries! (circular) - Maxton, James, 1885-1946 ; Brockway, Fenner, 1888-1988 ; McNair, John, 1887-1968; Maxton, James, 1885-1946 (1938)
1938 024_0018_002 292/946/24/18(ii)